Produção de eletrodos em carbono vítreo monolítico e reticulado a partir da resina furfurílica dopada com cobre - Ciavarelli, Vivian Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The glassy carbon is a material with a huge technological evolution. Due to its lightness, biocompatibility and their thermal and electrical properties this material finds applications in several industrial fields such as electronics, medical, aerospace and chemical. In order to explore the conductive properties of glassy carbon for use as modified electrodes, the present work aims the processing of monolithic and reticulated glassy carbon with colloidal copper for use in electrochemical applications. First, the best parameters for the cure of furfuryl alcohol resin doped were established through viscosimetry measurements and pressurized differential scanning calorimetry. The analysis of the micrographs of the cured resins show that copper concentrations above 3% weight, generate higher porosity in the material. The characterizations of the monolithic and reticulated glassy carbon resulting from carbonization were performed by scanning electron microscopy (SEM), Raman and Electrochemical impedance spectroscopy, and although it was not possible to detect the presence of copper by SEM, the influence of these particles have been observed by Raman and FT-IR spectra and electrochemical behavior of the material. The decrease in conductivity of monolithic and reticulated glassy carbon in the presence of copper may be related to the defects caused by the presence of copper in the structure of the material.

O carbono vítreo é um material carbonoso com ampla evolução tecnológica. Devido à sua leveza, biocompatibilidade e suas propriedades térmicas e elétricas este material encontra aplicações em diversas áreas industriais como a eletrônica, médica, aeroespacial e química. Com a finalidade de explorar as propriedades condutoras do carbono vítreo para a sua utilização como eletrodos modificados, o presente trabalho visa o processamento do carbono vítreo monolítico e reticulado dopado com cobre coloidal para uso em aplicações eletroquímicas. Primeiramente, foram estabelecidos os melhores parâmetros para a cura da resina furfurílica dopada por meio de medidas viscosimétricas e de calorimetria exploratória diferencial pressurizada. As análises das micrografias das resinas curadas com cobre mostram que concentrações acima de 3% em massa, geram maior porosidade no matérial. As caracterizações do carbono vítreo reticulado e monolítico resultantes da carbonização foram realizadas por meio da microscopia eletrônica de varredura (MEV), Raman e espectroscopia de impedância eletroquímica e, embora não tenha sido possível detectar a presença de cobre por MEV, verificou-se a influência deste nos espectros Raman, FT-IR e no comportamento eletroquímico do material. A diminuição na condutividade do carbono vítreo monolítico e reticulado na presença de cobre pode estar relacionado com os defeitos causados pela presença destes na estrutura do material
Keywords: Eletrodo de carbono; Eletroquimica; Carbono; Materiais carbonaceos; Furfuryl alcohol resin; Monolitic glassy carbon; Electrochemical properties